Smart Recognition and Apprise System With IoT - P.Baskaran, Aasim Ahmed S R, Abbas Yusuf, Deeptanshu Bordoloi (International Journal of Control and Automation, 2020)
Surveillance is the process of overlooking, controlling and monitoring a scenario, a particular place or a human being. This generally takes place in a military scenario where monitoring of borderlines and enemy territory is essential to a country’s safety. The surveillance and remote security system is a highly prominent feature on the mobile device. As the concept of internet of things is newly introduced in the field of electrical and electronics engineering. The concept is basically about managing the things with the use of internet and the most suited model for these kinds of applications is the Raspberry Pi. The highest priority is always given to Automation and Surveillance all over the world. Devices such as the surveillance robots are used worldwide to provide security at home as well as offices. This paper presents the monitoring and controlling of surveillance system enhanced with WI-FI module technology.  This system consists of webcam device and Raspberry Pi microcontroller. In this system, webcam device is used to detect the motions and smoke sensor is used to sense fire. The possibility of human movement is checked whether it is taking place or not then; the webcam device will record video of the live data in the surrounding and transmit the stream to the network through WI-FI module. Simultaneously, the buzzer device alerts the nearby neighbors. The system also consists of sprayer, which sprays the chloroform liquid on the intruders who have entered.